The Coding and Inter-Manual Transfer of Movement Sequences - Shea, Charles H.; Kovacs, Attila J.; Panzer, Stephan (Frontiers in Psychology, 2011)
The manuscript reviews recent experiments that use inter-manual transfer and inter-manual practice paradigms to determine the coordinate system (visual-spatial or motor) used in the coding of movement sequences. The results indicated that multi-element movement sequences are more effectively coded in visual-spatial coordinates even following extended practice, while very early in practice movement sequences with only a few movement elements and relatively short durations are coded in motor coordinates. Likewise, inter-manual practice of relatively simple movement sequences show benefits of right and left limb practice that involves the same motor coordinates while the opposite is true for more complex sequences. The results suggest that the coordinate system used to code the sequence information is linked to both the task characteristics and the control processes used to produce the sequence. These findings have the potential to greatly enhance our understanding of why in some conditions participants following practice with one limb or observation of one limb practice can effectively perform the task with the contralateral limb while in other (often similar) conditions cannot.